Faktor-Faktor yang Memengaruhi Profitabilitas pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2025 - Aprelia Nur Kumalasari; Sugeng Dwi Hartantyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The main objective of a company is to achieve provitability. In this study, profitability is measured using Return On Asset (ROA). The aim of this research is to determine the partial and simultaneous effects of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL) on Return On Asset (ROA) in banking companies listed on the Indonesia Stock Exchange (IDX) from 2022-2022. This research is a quantitative study, with sample selection using the purposive sampling method. The sample used consists of 42 banking companies over the period 2022-2022, and the data type is annual financial reports of banking companies listed on the IDX from 2022-2022. This study employs data analysis techniques including descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination, t-test, and F-test. The result of this study indicate that partially, the Capital Adequacy Ratio (CAR) has a significant negative effect on Return On Asset (ROA), the Loan to Deposit Ratio (LDR) have a significant positive effect on ROA, and Non Performing Loan (NPL) have a significant negative effect on ROA in banking companies listed on the IDX from 2022-2022. Simultaneously, the values of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL) have a significant effect on Return On Asset (ROA) in banking companies listed on the IDX from 2022-2022. This is evidenced by the significance value of 0,001, which is less than 0,05 or 0,001 < 0,05